(untitled) (Research, Society and Development, 2021)
An integrative review was carried out, aiming to identify which strategies to learning assessment are being applied to nursing students of higher education. The research was guided by the PICO strategy: what is the effectiveness of evaluative interventions available in the scientific literature on the strategies for learning assessment applied to nursing students at university level? The search for studies was performed between January and February 2019 in the following databases: LILACS, Medline, Scielo, BDENF, PubMed, CINAHL and Scopus. 24 references were included, and eight assessment strategies were identified. Most cited assessment in practices, followed by feedback, theoretical assessment, peer evaluation, self-assessment, group work assessment and, finally, qualitative assessment. It was noted that 75% (n=18) of the included studies were carried out outside the Brazilian scenario. Of the international studies, 20.8% are concentrated in the United Kingdom, 12.5% ​​in Hong Kong and 12.5% ​​in Ireland. In Brazil, studies were concentrated in the southeast region, with 12.5% ​​in São Paulo and 8.3% in Minas Gerais. As for the method used, 66% of the papers had a qualitative approach, 20.8% used a quantitative method and 20.8% used a mixed method with a quantitative and qualitative approach. Finally, this study identified as the main assessment tools used in higher education in nursing: assessment in practices, feedback, portfolio, theoretical assessment, peer evaluation, self-assessment, group work assessment and qualitative assessment. It is suggested to accomplish national studies, in order to broaden the discussions and improve the applied assessment techniques.